Exploring the possible health consequences of job insecurity: a pilot study among young workers - Fabrizio Bert; Maria Rosaria Gualano; Robin Thomas; Guglielmo Vergnano; Gianluca Voglino; Roberta Siliquini (Elsevier, 2020)
Objective: Socio-economical changes in Europe are leading to the rise of new issues regarding the labour market and health of young workers. Job insecurity is a widely studied phenomenon that involves an increasing number of young workers. We investigated its association with mental health and hazardous behaviours. Method: In this pilot study, 504 subjects aged between 18 and 40 were interviewed. STROBE guidelines were used. Socio-economic factors were evaluated. Adapted forms of validated scales were used to assess depression, anxiety disorder, alcohol and drug abuse and smoking habit. Univariate and multivariate analyses were performed. Results: Job insecurity appeared to be partially connected with the type of employment. Most respondents with a permanent contract felt their situation was secure, while this proportion was reduced when referring to temporary jobs and other kinds of contract (p < 0.001). Job security perception was associated with depression, anxiety, alcohol abuse and smoking habit (p < 0.001). Conclusions: Job security perception appears to be the most important predictive factor for the presence of depression and anxiety symptoms, alcohol consumption and smoking habit compared to other socio-economic factors under study. Resumen: Objetivo: Los cambios socioeconómicos en Europa están provocando el surgimiento de nuevas cuestiones sobre la salud de los trabajadores jóvenes. La inseguridad laboral es un fenómeno que involucra una cantidad creciente de trabajadores jóvenes. Nuestro estudio tiene como objetivo investigar la asociación entre inseguridad laboral y salud mental y comportamientos peligrosos. Método: En este estudio piloto fueron entrevistados 504 sujetos con edades comprendidas entre 18 y 40 años. Se evaluaron los factores socioeconómicos. Se usaron formas adaptadas de escalas validadas para evaluar la depresión, la ansiedad, el abuso de alcohol y drogas, y el hábito de fumar. Se realizaron análisis univariados y multivariados. Resultados: La mayoría de los encuestados con contrato permanente consideró que su situación era segura, mientras que esta proporción se redujo al referirse a trabajos temporales y otros tipos de contrato (p < 0,001). La percepción de la seguridad laboral se asoció con la depresión, la ansiedad, el abuso de alcohol y el hábito de fumar (p < 0,001). Conclusiones: La percepción de la seguridad laboral parece ser el factor predictivo más importante para la presencia de síntomas de depresión y ansiedad, el consumo de alcohol y el hábito de fumar, en comparación con otros factores socioeconómicos en estudio.